2019
DOI: 10.1159/000504443
|View full text |Cite
|
Sign up to set email alerts
|

Midstream Clean-Catch Urine Culture Obtained by Stimulation Technique versus Catheter Specimen Urine Culture for Urinary Tract Infections in Newborns: A Paired Comparison of Urine Collection Methods

Abstract: Objective: The group of Herreros Fernández developed a new, safe, quick, and successful technique for collecting midstream clean-catch urine(MS-CCU) in newborns based on bladder stimulation and lumbar paravertebral massage maneuvers. The purpose of this study was to compare the contamination rates of catheter specimen urine (CSU) and MS-CCU by a lumbar/sacral stimulation technique in newborns. Materials and Methods: Full-term newborns ranging in age from 2 to 28 days who needed an investigation for a presumed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In most previous studies, the reported contamination rate was lower, but the study design, definition of a positive urine culture, interpretation of low bacterial count, rate of circumcision, indication for the test, and the patient's age group were variable ( 4 , 9 11 , 13 , 15 ). In a retrospective study among older infants (2–24 months of age) in our pediatric department, we found a lower catheter-obtained urine culture contamination rate of 17%: 14% among boys and 18% among girls (unpublished data), emphasizing the higher contamination risk in very young infants.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…In most previous studies, the reported contamination rate was lower, but the study design, definition of a positive urine culture, interpretation of low bacterial count, rate of circumcision, indication for the test, and the patient's age group were variable ( 4 , 9 11 , 13 , 15 ). In a retrospective study among older infants (2–24 months of age) in our pediatric department, we found a lower catheter-obtained urine culture contamination rate of 17%: 14% among boys and 18% among girls (unpublished data), emphasizing the higher contamination risk in very young infants.…”
Section: Discussionmentioning
confidence: 93%
“…No other study has showed such a low contamination rate. In two small prospective studies among neonates, the contamination rate of catheter-obtained urine culture was 10–22% ( 4 , 15 ). In agreement with our results, Wingerter et al showed the same contamination rate among infants <6 months, while using the same definition of contamination ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations